Peningkatan Keterampilan Sosial melalui Model Problem Based Learning Berbantuan PPt Interaktif Mata Pelajaran Pendidikan Pancasila pada Peserta Didik kelas V Sekolah Dasar - Putri Shofik Alfiatun; Siti Istiyati (Universitas Sebelas Maret, 2025)
This study aims to improve the social skills of students using a problem-based learning model assisted by Interactive PPt in Pancasila Education subjects at SDN Ngebung 1 Sragen in the 2024/2025 school year. This research is a class action research that was carried out as many as 2 cycles using the Kemmis and MC method. Taggart method including planning, implementation, observation, and reflection. The results showed that the social skills of students using the PBL model assisted by Interactive PPt increased in Pancasila Education subjects. In the pre-action, the social skills of students amounted to 24%, increased in cycle I to 47% and increased in cycle II by 85.2%. The aspects of social skills used in this study include peer relationship skills, self-management skills, academic skills, compliance skills, and assertive behavior.